The bioguided fractionation and pharmacological activity of an endemic Salix canariensis species - Gutiérrez Sandra Dévora; Kuri Susana Abdala; Martín-Herrera Domingo (Acta Pharmaceutica)
The present study was designed to confirm the wide traditional use of treating pain with Salix canariensis, an endemic species of the Macaronesian region. The active compounds were identified. Pharmacological activities were explored in experimental animals by acetic acid-induced writhing, formalin and Levy’s tests, and bioactive compounds were identified after a bio-guided fractionation of the most active organic extract. S. canariensis extract, orally administrated at different doses, led to a significant reduction in writhing, caused a moderate decrease of formalin-induced pain and revealed an excellent dose-dependent anti-inflammatory effect. Bioassay-guided fractionation of the ethyl acetate extract suggested the possible presence of pentacyclic triterpenes from oleanane and ursane series. These findings allow the conclusion that S. canariensis exerts analgesic and anti-inflammatory activities, documenting its traditional use in the treatment of pain and inflammatory diseases.